MENSYARIAHKAN AKUNTANSI KONVENSIONAL (An-Nisbah: Jurnal Ekonomi Syariah, 2017)
Abstract:  Structure of accounting theory describes the composition, the overall hierarchy of fnancial accounting concepts. Structure of accounting theory is infuenced by the economMic system, social ideology embraced by the community. The structure of the conventional accounting theory was born of American society by the capitalist economic system with a range of properties and social systems such as democracy, liberalism, secularism competition, scientifc and other characteristics that are different from the concept of Islamic theory that laid the foundation of Islam on the basis of moral and material aspects of life and build economic strength in ethical values    and moral and spiritual dimensions. Conventional accounting theory concepts that exist today can be used as a basis for adopting the syari’a accounting. The role of Muslim intellectuals in the Islamization of conventional accounting is pretty cut that does not comply with Islamic Shari’a and the need to add additional emphasis to the purpose of sharia (maqasid as-sharia). The Holy Qur’an says that truth is only from Allah (al haqqu min robbikum). If conventional accounting born of natural law and syari’a accounting inspired by the Qur’an, they are able to co-exist in the birth of the concept of human welfare and the whole of nature.  Accounting trends emerging lately proving similarity with conventional accounting direction that syari’a accounting methods made     possible the adoption and modifcation. Accounting with syari’a values    will be able to make a signifcant contribution to the advancement of the accounting world. Islam as rahmatan li al-alamiin should also be providing accounting concepts that are benefcial for the entire universe.Keyword: accounting, conventional, syariah